Isomerization of Asp residues plays an important role in αA‐crystallin dissociation. (21st January 2016) - Takata, Takumi; Fujii, Noriko
Abstract : Aged cataract formation is caused by the accumulative precipitation of lens proteins incorporating diverse post‐translational modifications. α‐Crystallin, a major structural and functional lens protein, consists of a large polymeric structure that is dissociated and insolubilized with accumulative post‐translational modifications. One such modification, isomerization of Asp, was recently identified in αB‐crystallin monomers derived from aged lens. However, the distributions of Asp isomers in each lens fraction remain unknown. Here, α‐crystallin fractions from aged lens were separated into heteropolymeric and monomeric forms to determine the Asp isomerization ratios in each fraction. Lens of four different ages were homogenized and centrifuged, and the soluble fraction was applied to size‐exclusion chromatography. The heteropolymeric α‐crystallin and monomeric crystallin fractions were obtained and concentrated. After trypsin digestion, each fraction was independently applied to liquid chromatography equipped with mass spectrometry to extract α‐crystallin‐derived peptides containing Asp isomers. The results showed that Asp58, Asp84 and Asp151 of αA‐crystallin were highly isomerized in the monomeric fraction, but not isomerized to the same level in the heteropolymeric fraction. Each type of Asp isomerization increased in an age‐dependent manner, was site‐specific and was similar to previous results from lens water‐insoluble fractions. These results imply that isomerization of Asp residues leads to dissociation of αA‐crystallin from the heteropolymeric state and induces insolubilization in aged lens. Taken together, our findings suggest that isomerization of Asp might disrupt the higher order polymeric state of α‐crystallin, resulting in decreased solubility and function, ultimately contributing to lens protein impairment and cataract formation with aging. Abstract : α‐Crystallin, one of the major eye lens protein, is a stable polymer consisting of two subunits, αA‐ and αB‐crystallins. When normal Lα‐Asp 58, 84, 151 residues in αA‐crystallin are isomerized to abnormal Lβ‐Asp, Dα‐Asp and Dβ‐Asp with age, the α‐crystallin hetero‐polymer would be dissociated to monomer, followed by senile cataract formation.